IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATAKULIAH BAHASA INDONESIA - Novi Eka Susilowati (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Character is one of the big problems faced by Indonesia because currently Indonesia is considered experiencing moral degradation. Therefore, cha- racter education should be applied in every level of education to improve the morale ofstudents. Character education needs to be done because (1) decline in family function, (2) the worsening morale of the young genera- tion, (3) the declining value of ethics. With this in mind, the application of character education to Indonesian subjects is very relevant and strate- gic to do because Indonesian is a compulsory course that must be followed by all students. Implementation of character education in Indonesian subjects is conducted in an integrated manner in the planning, imple- mentation, and assessment of learning. Character education is expected to shape the character of the students so that universities not only produce graduates who excel in terms of cognition, but also in terms of behavior.